Religious Digital Literacy and Prevention of Radicalism in Schools - Khakim, Muhammad Khakim Ashari (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2024)
Religious digital literacy is an urgent need for students in this era. The influence of digital information is very large on religious understanding and practice because digital product users are now free to access whatever information they need. This research aims to determine religious digital literacy practices and prevent radicalism in schools. This research uses a systematic literature review approach whose main sources are relevant books and scientific journals. This research shows that religious digital literacy practices are carried out using relevant religious digital learning sources. This is done to provide easy access for students so they can improve their understanding and critical thinking. This religious digital literacy practice also requires supervision and assistance from teachers and parents. Preventing radicalism in schools can be done by training students' critical thinking skills in accessing and using all available digital information so that all information obtained is well validated.